Optimalisasi Kesadaran Merek Resto Oemah Gechok Melalui Perancangan dan Sosialisasi Brand Guideline - Purbaya, Muhammad Eka; Hidayat, Chusnul Maulidina; Marsally, Silvia Van; Azzam, Abyan Naufal (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2025)
Oemah Gechok Restaurant, located 350 meters from Saka Tunggal, is a local culinary business owned by the Village-Owned Enterprise in Cikakak, Wangon, Banyumas, which serves the traditional dish Ayam Gechok. Despite its great potential, Oemah Gechok Restaurant faced issues of low brand awareness and customer engagement, which could hinder its growth and sustainability. This service project focused on efforts to improve Oemah Gechok’s visibility and competitiveness through the design of a strong visual identity and the implementation of digital marketing strategies. The goal of this project was to strengthen the brand image and expand market reach. The methods used included the development of brand guidelines, logo creation, activation of Google Maps and Instagram, as well as training for the business managers. The results of this project showed a significant increase in customer interaction, with Instagram account reach increasing by 300% and content impressions rising by 1,720%. Satisfaction surveys indicated that the training successfully enhanced the knowledge and skills of the managers, positively impacting business management. The impact of this project not only increased brand awareness but also made a tangible contribution to supporting local economic growth through more effective and sustainable marketing strategies.